Coronary vasospasm induced by aminophylline after negative dipyridamole stress echocardiography: a case report - Lauro Cortigiani; Davide Donelli; Francesco Bovenzi (Exploration of Cardiology)
We report the case of a 58-year-old patient with chronic ischemic syndrome who underwent dipyridamole stress echocardiography for the evaluation of chest pain. The stress test was negative with normal coronary flow velocity reserve, preserved chronotropic competence, and no inducible wall motion abnormalities. However, upon administration of aminophylline at the end of the test, the patient developed acute chest pain, ST-segment elevation, and severe apical wall motion abnormalities. These findings resolved with intravenous nitrates. Subsequent coronary angiography revealed a significant vasospastic stenosis in the left anterior descending artery superimposed on a mild organic stenosis of around 50% after intracoronary nitrates. The coronary stenosis was successfully treated with a drug-eluting stent. This case highlights the potential for vasospastic angina to be unmasked following vasodilator reversal, even after a negative stress echocardiography.